Homatula wuliangensis (Teleostei: Nemacheilidae), a new loach from Yunnan, China - Min, Rui; Yang, Jun-Xing; Chen, Xiao-Yong (Zootaxa, 2012)
A new species of Homatula, Homatula wuliangensis, is described from the Lancang River of the Wuliang Mountain, Pu-Er City, Jingdong County, Yunnan Province, China. Homatula wuliangensis sp. nov. is readily distinguished from otherspecies of Homatula by the combination of several morphological characters, including a long upper lobe of the caudalfin relative to the lower lobe, high and long dorsal adipose crest, series of 22–26 very closely aligned body markings, bodyscaled, and 41–42 vertebrae. In addition, H. wuliangensis differs from the similar species H. anguillioides in having short-er barbels, spots on the caudal fin, the origin of the pelvic fin under the last simple dorsal-fin ray, and a pointed axillarypelvic lobe divided from the body. The new species is further distinguished from the similar species H. pysnolepis in having shorter barbels, lacking a notch on the lower jaw, and lacking vermiform markings on top of the head.